Iridium/N-heterocyclic carbene-catalyzed C–H borylation of arenes by diisopropylaminoborane - Tobisu, Mamoru; Igarashi, Takuya; Chatani, Naoto (Beilstein Journal of Organic Chemistry, 2016)
Catalytic C–H borylation of arenes has been widely used in organic synthesis because it allows the introduction of a versatile boron functionality directly onto simple, unfunctionalized arenes. We report herein the use of diisopropylaminoborane as a boron source in C–H borylation of arenes. An iridium(I) complex with 1,3-dicyclohexylimidazol-2-ylidene is found to efficiently catalyze the borylation of arenes and heteroarenes. The resulting aminoborylated products can be converted to the corresponding boronic acid derivatives simply by treatment with suitable diols or diamines.
Keywords: boronic acid; C–H borylation; iridium; N-heterocyclic carbene

(untitled) - Mkhalid, I. A. I.; Barnard, J. H.; Marder, T. B.; Murphy, J. M.; Hartwig, J. F. (Chem. Rev., 2010)

(untitled) - Ishiyama, T.; Takagi, J.; Ishida, K.; Miyaura, N.; Anastasi, N. R.; Hartwig, J. F. (J. Am. Chem. Soc., 2002)

(untitled) - Hatanaka, T.; Ohki, Y.; Tatsumi, K. (Chem. – Asian J., 2010)

(untitled) - Yan, G.; Jiang, Y.; Kuang, C.; Wang, S.; Liu, H.; Zhang, Y.; Wang, J. (Chem. Commun., 2010)

(untitled) - Dombray, T.; Werncke, C. G.; Jiang, S.; Grellier, M.; Vendier, L.; Bontemps, S.; Sortais, J.-B.; Sabo-Etienne, S.; Darcel, C. (J. Am. Chem. Soc., 2015)

(untitled) - Mazzacano, T. J.; Mankad, N. P. (J. Am. Chem. Soc., 2013)
See for Cu–Fe mixed catalyst.

(untitled) - Obligacion, J. V.; Semproni, S. P.; Chirik, P. J. (J. Am. Chem. Soc., 2014)

(untitled) - Furukawa, T.; Tobisu, M.; Chatani, N. (Chem. Commun., 2015)

(untitled) - Zhang, H.; Hagihara, S.; Itami, K. (Chem. Lett., 2015)

(untitled) - Furukawa, T.; Tobisu, M.; Chatani, N. (J. Am. Chem. Soc., 2015)

(untitled) - Takaya, J.; Ito, S.; Nomoto, H.; Saito, N.; Kirai, N.; Iwasawa, N. (Chem. Commun., 2015)

(untitled) - Légaré, M.-A.; Courtemanche, M.-A.; Rochette, É.; Fontaine, F.-G. (Science, 2015)

(untitled) - Ros, A.; Fernández, R.; Lassaletta, J. M. (Chem. Soc. Rev., 2014)
See for a review.

(untitled) - Kuninobu, Y.; Ida, H.; Nishi, M.; Kanai, M. (Nat. Chem., 2015)
See for directed meta-borylation.

(untitled) - Saito, Y.; Segawa, Y.; Itami, K. (J. Am. Chem. Soc., 2015)

(untitled) - Tzschucke, C. C.; Murphy, J. M.; Hartwig, J. F. (Org. Lett., 2007)

(untitled) - Liskey, C. W.; Hartwig, J. F. (Synthesis, 2013)

(untitled) - Liskey, C. W.; Wei, C. S.; Pahls, D. R.; Hartwig, J. F. (Chem. Commun., 2009)

(untitled) - Iwadate, N.; Suginome, M. (J. Organomet. Chem., 2009)

(untitled) - Noguchi, H.; Hojo, K.; Suginome, M. (J. Am. Chem. Soc., 2007)

(untitled) - Köster, R.; Bellut, H.; Hattori, S. (Justus Liebigs Ann. Chem., 1968)

(untitled) - Euzenat, L.; Horhant, D.; Ribourdouille, Y.; Duriez, C.; Alcaraz, G.; Vaultier, M. (Chem. Commun., 2003)

(untitled) - Pasumansky, L.; Haddenham, D.; Clary, J. W.; Fisher, G. B.; Goralski, C. T.; Singaram, B. (J. Org. Chem., 2008)

(untitled) - Marciasini, L.; Richy, N.; Vaultier, M.; Pucheault, M. (Chem. Commun., 2012)

(untitled) - Marciasini, L. D.; Richy, N.; Vaultier, M.; Pucheault, M. (Adv. Synth. Catal., 2013)

(untitled) - Guerrand, H. D. S.; Marciasini, L. D.; Jousseaume, M.; Vaultier, M.; Pucheault, M. (Chem. – Eur. J., 2014)

(untitled) - Marciasini, L.; Cacciuttolo, B.; Vaultier, M.; Pucheault, M. (Org. Lett., 2015)

(untitled) - Tobisu, M.; Yasutome, A.; Kinuta, H.; Nakamura, K.; Chatani, N. (Org. Lett., 2014)

(untitled) - Tobisu, M.; Takahira, T.; Ohtsuki, A.; Chatani, N. (Org. Lett., 2015)

(untitled) - Tobisu, M.; Takahira, T.; Chatani, N. (Org. Lett., 2015)

(untitled) - Tobisu, M.; Morioka, T.; Ohtsuki, A.; Chatani, N. (Chem. Sci., 2015)

(untitled) - Morioka, T.; Nishizawa, A.; Nakamura, K.; Tobisu, M.; Chatani, N. (Chem. Lett., 2015)

(untitled) - Nakamura, K.; Tobisu, M.; Chatani, N. (Org. Lett., 2015)

(untitled) - Frey, G. D.; Rentzsch, C. F.; von Preysing, D.; Scherg, T.; Mühlhofer, M.; Herdtweck, E.; Herrmann, W. A. (J. Organomet. Chem., 2006)

(untitled) - Ishiyama, T.; Ishida, K.; Takagi, J.; Miyaura, N. (Chem. Lett., 2001)

(untitled) - Larsen, M. A.; Wilson, C. V.; Hartwig, J. F. (J. Am. Chem. Soc., 2015)